Prinsip Ubat-Ubatan Nabawi Menurut Mahmud Nazhim Al-Nasimi: Principles of Prophetic Medicine According to Maḥmūd Nāẓim al-Nasīmī - Muhammad Akmalludin Mohd Hamdan (Maʿālim al-Qurʾān wa al-Sunnah, 2023)
Prophetic medicine presents various methods of treatment and disease prevention recommended by the Prophet Muhammad (peace be upon him). He is seen advising the use of specific natural ingredients such as honey, dates, and black seed (al-ḥabbat al-sawdāʾ) to his companions as a solution to their health issues. In recent times, some individuals have exploited the sanctity associated with the words of the Prophet Muhammad (peace be upon him) for the purpose of promoting their products containing ingredients mentioned in the hadith. Certain traders who sell these ingredients directly have also been observed to publicise their businesses using the same modus operandi. Moreover, some general statements from the sayings of the Prophet (peace be upon him) have been used indiscriminately to capture the interest of buyers without relying on the understanding of Islamic scholars and modern medical experts when dealing with relevant hadith. The purpose of this article is to highlight the fundamentals of prophetic medicine as described in Maḥmūd Nāẓim al-Nasīmī ‘s book al-Ṭibb al-Nabawī wa al-ꜥIlm al-Ḥadīth. The analysis is carried out through a deductive approach and a comparison of the principles he proposed with the commentary of Islamic scholars in their hadith lecture works. The study found that al-Nasīmī’s claims about prophetic medicine, like the idea that it includes both revelation and ijtihad (independent reasoning), are in line with what some early Islamic scholars thought.